Warriors and Wizards : the Development and Defeat of Radio-Controlled Glide Bombs of the Third Reich. - Bollinger, Martin (Naval Institute Press, 2011)
In August 1943 the Luftwaffe began using radio-controlled anti-ship glide bombs, and within weeks they had sunk one battleship, crippled another, wrecked two cruisers, and destroyed numerous merchant ships. Yet a year later the Germans abandoned their use, defeated in part by electronic systems to jam the radio links that guided the bombs. Drawing on a wealth of new sources, Martin Bollinger examines what happened from both a historical and technological perspective and lays out a mission-by-mission analysis of effectiveness. Based on interviews with participants, intelligence documents, and a.